Pemberdayaan Karang Taruna : Optimalisasi Melalui Program Pelatihan Pagu Usulan Partisipatif Masyarakat (PUPM) Di Kabupaten Sleman - Kirana Rilla Pratama (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The aim of this research is to find out how optimal training is based on the community participatory proposed ceiling program (PUPM) for youth organizations that has been carried out in Sleman Regency. The research method used is descriptive qualitative. The research concluded that the empowerment of youth organizations through the community participatory proposed ceiling training program (PUPM) could be said to be not optimal because there were still several things that had not been paid attention to, such as a lack of careful planning (target age, implementation time, no monitoring and evaluation, and opportunities for applying knowledge obtained) as well as the lack of awareness of youth organization members regarding the use of programs provided by the government.